Green Accounting Analysis (Reduce, Reuse, Recycle) to Improve Financial Performance: a Case Study of Kud Tani Bahagia 1 Mojokerto - Hamdani, Helmi Difa; Leniwati, Driana; Setyawan, Setu; Jati, Ahmad Waluya; Affan, Muhammad Wildan (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to implement the concept of 3R Green Accounting, namely (Reduce, Reuse, Recycle) by using an interpretive paradigm, this study tries to interpret the 3R concept whether it affects financial performance with a case study design, and the research combines 3 concepts in green accounting, namely, environmental costs, social costs, and economic costs in the implementation of green Accounting in KUD Tani Bahagia 1. The data was obtained by conducting in-depth interviews with employees at KUD and the surrounding community. The results of the interviews were grouped and the data was simplified before being analyzed and conclusions drawn. This in-depth research also reveals whether there are costs caused by the 3R concept and whether it will affect the financial performance of KUD. By considering the principles in accounting. Keywords : Green Accounting; 3R (Reduce, Reuse, Recycle); Financial Perfomance;